rHDPE-rPP Hybrid Blends From Injection Molding Scrap : Characterization For Conventional Milling Workpiece Application - Wahid, Siti Zaleha (2017)
Various ratio combinations for two difference polymeric phases could enhance the resulted properties of newly developed miscible blends. The blend could possess higher strength characteristic that would beneficial for various engineering applications. In this study, scrapped from injection molding IM) operation is recycled for polymeric blend development. Recycling of polymeric waste helps to conserve the natural resources and environment by reducing the utilization of hydrocarbon. Up to now, specific research focusing on the blend made from recycled high density polyethylene (rHDPE) and recycled polypropylene (rPP) due to IM waste are really scarce. Hence, this research has been conducted to develop and formulate the optimum rHDPE/rPP blends for conventional milling operation. This to replace the utilization of an expensive Delrin or steel machining block for teaching and learning purposes in IKTBN Pagoh and IKTBN Sepang, Malaysia. At first, the prime investigation is to evaluate the performance of rHDPE/rPP blends and their correlation between miscibility effects with the resulted mechanical properties of hybrids at various blends ratio. The rHDPE/rPP blends are produced by crushing both rHDPE and rPP materials, followed by secondary mixing via an extrusion process, as to ensure well-mixing of rHDPE/rPP hybrid at their respective formulation ratio. Different ratio of rHDPE/rPP (0/100 wt.%, 30/70 wt.%, 50/50 wt.%, 70/30 wt.%, 100/0 wt.%) are used to investigate the effects of materials phases towards the resulted mechanical, thermal and physical properties of rHDPE/rPP blends. Later, the fracture surface morphology of the selected rHDPE/rPP m blend samples are analysed through Scanning Electron Microscopy (SEM) observation. In addition, the melting temperatures (Tm) of rHDPE/rPP samples are measured by Differential Scanning Calorimeter (DSC) technique for miscibility evaluation through thermal route. At the end of this study, rHDPE/rPP blend with higher strength and thermal performances is proposed for substituting the Delrin material for machining application. It was found that the 70/30 wt.% of rHDPE/rPP was significantly possessed outstanding mechanical and physical characteristic in terms of their tensile, elongation at break and the hardness behaviour, as well as better thermal properties improvement. The 70/30 of rHDPE/rPP blend has yielded an extraordinary improvement at about 59.8% in their tensile strength, 473% of elongation at break and 2.3% of the hardness improvements. It was also found that there are two Tm peaks appeared in the total heat flow curve for all formulated blends which indicates the immiscible nature of produced blends. The range of Tm was found gradually decreased when the portion of rHDPE phase is increased up to 100 wt.%. At the end, this research has significantly important to be carried out as to provide another alternative candidate for cost saving machining materials in teaching and learning purposes. This new candidates of rHDPE/rPP blend material produced from recycled IM by-product are also environmental friendly and will not cause pollution or any harm toward the environment.